Prarancangan Pabrik N-Metilanilin Kapasitas 38.000 Ton/Tahun - Robiansah, Dapid; Haryanto, Haryanto; Fuadi, Ahmad M (2017)
This research aims to know the prarancangan N-Metilanilin Factory capacity of 38,000 tons/year. The results showed. The results showed a profit before tax of Rp 346.347.211.207, 47per years. Profit after tax of Rp 242,443,047,845.23 per year. ROI (Return On Investment) before tax 45.13%. ROI after tax 31.59%. The ROI before tax for high-risk factories at least 44%. POT (Pay Out Time) before tax of 1.81 years. The POT after the tax year 2.40. POT before tax for high-risk factories a maximum of 2 years. BEP (Break Even Point) is 44.59% and SDP (Shut Down Point) is 26.26%. BEP for chemical plant generally range between 40%-60%. DCF (Discounted Cash Flow) is 38.69%. Based on the consideration that the ROI, BEP, and DCF to mills at high risk due to a pressure above atmospheric pressure operations however the calculation standards, so the factory N-Metilanilin is worth to set up.